Automated Warehouse Management Wagon Depot - Nurmukhamedov, Tolaniddin Ramziddinovich (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: The research paper provides an analytical review of the rational organization of storage in transport, notes the works of scientists that are of great importance for the railway industry, and considers the issues of optimal placement of inventory items in the carriage depot of the Joint Stock Company "Uztemiryulyulovchi" ("Uzdzheldorpass"). The structure of a warehouse reflecting the main elements of technological sections, consisting of an unloading section, a cargo receiving section, a storage area (temporary and main), a picking section, a service and technical room, is presented. The developed mathematical models for determining rational placement, graphs of the effect of the life cycle of goods on the logistics cycle of replenishment of stocks, methods for determining the amount of supply of spare parts for mobile units when managing their stocks are presented.